P-OGC64 High Fidelity Patient-Reported Outcome Monitoring following Upper Gastrointestinal and Hepato-Pancreato-Biliary Cancer Surgery. Early Experience with a Novel Application. (16th December 2021) - Milner, George; Jessel, Irene; Ho, Natalie; Robert O'Neill, J; Martin, Jack; Alagarsamy, Famila; Baker, Tim
Abstract: Background: Patients undergoing complex upper-gastrointestinal and hepatopancreatobiliary resections experience a high incidence of post-operative symptoms. There is significant scope to expand clinicians' understanding of longitudinal symptom progression and recognise a greater range of post-operative symptoms than those traditionally recorded. By identifying symptoms most troublesome to patients we anticipate improvement in patients' symptom management, the surgical consent process and, ultimately, patient experience. The myICUvoice application provides patients with the opportunity to report symptoms across a wide range of domains in real-time. We report our early experience using this application with patients in the post-operative setting.  Methods: Following institutional governance approval,  consecutive patients undergoing  pancreatic, or hepatic (H) or oesophagogastric (U) resectional surgery during a four week period at a single tertiary centre were offered the opportunity to use the application. From day-1 post-op to discharge, each patient completed surveys at least twice daily, reporting their experience across a list of 34 symptoms together with pain, breathing, mood and physical state. Both individual and cohort time-series data were obtained for each symptom and stratified by resection type. A dashboard has been developed as part of the application to allow summary data to be easily displayed.   Results: 342 symptom surveys were completed by a total of 15 patients (5U, 10H).  The median length-of-stay was 11-days and 91% of patients completed 2 surveys/day (Table-1 ). High frequency symptoms were tiredness (reported in H:80%;U:86% of surveys), dry mouth (14/15 patients, H:91%, U:59%) and uncomfortable position (13/15 patients, H:27%, U:43%). Whilst most patients remained happy, there were frequent reports of psychological distress; 53% reported nightmares (H:6%, U:12% of surveys), 67% felt depressed, (H:12%, U:6% of surveys) and 53% anxious (H:14%, U:6% of surveys). Pain statement analysis (Figure-1 ) revealed distinct profiles providing high resolution data on the efficacy of analgesic regimes/techniques.  Conclusions: As expected, our patient cohort experienced a wide range, and high frequency, of post-operative symptoms. Experience conducting symptom surveys demonstrated a high incidence of disconnect between clinical expectations and reported symptoms. Our data illustrate the value of detailed symptom monitoring and this application could be used  routinely to measure and improve the patient experience. Further research is planned to compare the performance of these standardised symptom surveys to current methods of identifying symptoms. Furthermore, data from specific patient populations could better inform patient expectations of the post-operative symptoms they may experience, thus improving the surgical consent process.